Trusted measure model for the communication network system - Senxin ZHOU; Jianghong HAN; Yaohui ZHANG; Chao LI (Dianxin kexue)
The trusted measure model for communication was proposed by computing its value of security,control and survivability with continuous-time reward Markov method.The“state bomb”problem in traditional state analysis method was solved by the way of structural equation solution.The generic function optimization algorithm was used to reduce computational complexity.Simulation experiments show that the model is correct and feasible.